Designing Key Succession Planning Priorities for a Family-Owned Facility Service Company: A Case Study of PT EI in Indonesia - Putri, Eriana Mayutasya; Permana , Muhammad Yorga (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to identify the critical barriers influencing succession planning readiness at PT EI and to convert these barriers into strategic priorities for developing a practical succession planning roadmap. This research uses a qualitative method with a single case study approach. Data were gathered through semi-structured interviews with seven important informants from the family ownership and operational management levels. The interview results were analyzed using the Gioia Methodology through a three-stage coding process, where the aggregate dimensions were connected to the four premises of the Parallel Planning Process (PPP) framework developed by Carlock and Ward (2001). The findings were then prioritized using the Impact–Effort Matrix to determine the order of implementation. The study found nine critical barriers within the four PPP premises, which were mainly about an informal company culture, an ongoing leadership transition, a strong reliance on the founder, a vision and strategy that were not yet aligned, and a lack of formal systems for governance, operations, and human resources. These barriers were transformed into nine proposed strategies and grouped into six strategic priorities such as institutionalizing company culture, formalizing organizational structure, aligning shared vision, developing family governance, redesigning operational procedures, and creating a leadership development pipeline. Based on the Impact–Effort Matrix, the first three priorities were categorized as Quick Wins, while the other three were classified as Major Projects, creating roadmap priorities to improve PT EI’s succession readiness and long-term sustainability.